Baseline levels and spatial distribution of arsenic species in surface sediments of the East China Sea shelf - Tianyu Bian; Xiaoyong Duan; Bin Chen; Xingliang He; Shenghua Lv; Meina Li; Ke Cao; Fei Gao; Ping Yin (Marine Pollution Bulletin, 2026)

Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

Development of a sandwich ELISA analysis platform using dual nanobodies for quantitative detection of bovine lactoferrin in dairy products - Li Cao; Ting Zhang; Yan-Ping Li; Qinghua He; Zhui Tu (International Dairy Journal, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

GABA-enriched Lactobacillus buchneri XBMU-C1 fermentation broth lowers blood pressure in L-NAME-induced hypertensive rats via RAAS suppression and PI3K/Akt/eNOS activation - Dandan Gao; Chenchen Wang; Ying Chen; Jiwen Wang; Junyao Mei; Yujie Cao; Xuankang Yang; Shangyun Kang; Jinyong Ma; Ping Li (Food Research International, 2026)

Ecological risks of olivine with different particle sizes and dosages on planktonic ecosystems during ocean alkalinization - Zi-Rui Ding; Xin-Ming Wu; Ping Li; Xin-Yu Qian; Chang Liu; Ming-Hao Yin; Chun-Feng Qu; Zhihan Cao; Jinho Jung; Ling Liu; Zhi-Hua Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A divalent nanoparticle vaccine confers robust protective immunity against serotype O FMDV and SVA in pigs - Nan Cao; Yamei Li; Xinghua Chen; Hehai Li; Linxing Tian; Zihui Hu; Yin Bo; Feifei Diao; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Viable lactic acid bacteria across the production-food-gut continuum: Multi-stress adaptation and robustness engineering - Jing Cui; Jiahui Li; Meijuan Ran; Qi Chen; Jiehong Fang; Jiankang Jiang; Qing Cao; Ping Li; Han Jiang; Qing Gu (Trends in Food Science & Technology, 2026)

Intravenous Exposure to Amino-polystyrene Induces Excessive Autophagy and Apoptosis in Myocardium Through ROS Driven PI3K/AKT/mTOR Axis - Wen Gou; Yujun Xie; Rui Xia; Ping Gou; Chunfeng Cao; Fujun Luan; Beizhong Liu; Yuan Li (Cardiovascular Toxicology, 2026)

Drivers of greenhouse gas emissions from global coastal blue carbon ecosystems: a synthesis of methane and carbon dioxide fluxes - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Investigation on pipeline-backfill-trench lateral interaction in clay seabed - Jiefeng Liu; Haiying Cao; Ping Wang; Liang Liu; Enhua Zhang; Yunong Li; Jingyan Lan; Lei Wang (Soil Dynamics and Earthquake Engineering, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Comprehensive life-cycle assessment of a hybrid renewable energy system–powered decentralized sewage treatment system in cold and rural Inner Mongolia - Shangbin Ma; Ping Miao; Shugang Guo; Yaoting Hu; Hongli Ma; Pengyu Li; Pengfei Cao; Dawen Gao; Jing Luo; Jianguo Liu; Tianlong Zheng (Journal of Water Process Engineering, 2026)

Dynamic changes, flavor contributions, and enzymatic transformation mechanisms of phenolic acids during black tea processing - Anan Xu; Shanshan Wang; Qianhuang Xiao; Sixu Li; Zheng Tu; Meng Tao; Yanyan Cao; Qinwei Guo; Ping Xu; Zhengquan Liu (Food Chemistry, 2026)

Early Miocene Populus L. Fossils Reveal the Northwestward Expansion of the East Asian Summer Monsoon Into Eastern Qaidam - Zhen‐Dong Cao; San‐Ping Xie; Jing‐Nan Huang; Yun‐Zhe Zhang; Zi‐Yi Li; Si‐Hang Zhang; De‐Fei Yan (Journal of Biogeography, 2026)
Aim The evolution of the East Asian Summer Monsoon (EASM) is critical for understanding Asian biodiversity and ecosystem stability. While models and geological records suggest the EASM reached the Qaidam Basin during the Miocene, macrofossil evidence remains scarce. We aimed to test the hypothesis of a northwestward monsoon expansion using newly discovered Populus fossils as bioclimatic indicators. Location Wulan Basin, northeastern Tibetan Plateau, Qinghai Province, China. Taxon Angiosperms (Salicaceae: Populus L.). Methods We conducted morphological analyses on leaf fossils and identified their Nearest Living Relative (NLR). By establishing correlations between the leaf traits of the NLR and modern climatic factors, we reconstructed the paleoclimate of the Wulan Basin. Furthermore, we employed Species Distribution Modelling (MaxEnt) to simulate the potential range of this lineage under Early Miocene conditions to explore monsoon‐driven habitat shifts. Results The late Early Miocene fossils from the Wulan Basin are morphologically most similar to the extant Populus davidiana , a species characteristic of temperate, semi‐humid environments. The presence of this lineage indicates that the Wulan Basin—currently an arid region—experienced significantly higher precipitation and a temperate semi‐humid climate during the Early Miocene. MaxEnt modelling reveals that the suitable bioclimatic envelope for this Populus group extended much further northwest than its modern range, providing a potential biological signal of enhanced moisture transport into the interior of East Asia. Main Conclusions The occurrence of Populus fossils in the Wulan Basin provides a preliminary biological indicator for the northwestward expansion of the EASM into the northeastern Tibetan Plateau during the late Early Miocene, although corroboration from additional proxy records and localities is still needed. This climatic shift, likely driven by the phased uplift of the Tibetan Plateau, transformed the regional hydrological cycle and facilitated the migration of mesic woody taxa into Asia's interior. Our findings highlight the profound impact of tectonic‐monsoon interactions on historical plant distributions.

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

A Study on the Suitability of Operating Strategies for PV/T-Medium-to-Deep-Ground-Source Heat Pump Heating Systems Based on Peak-and-Off-Peak Electricity Rates - Dong Wei; Yu-ping Zhang; Quan-hui Liu; Yi-chao Zhao; Hao Wu; Sheng-ji Xu; Yu Cao; Jia-yuan Li; Ling-ling Bao (Applied Geophysics, 2026)

A new amide alkaloid from the coculture liquid cultures of two grape endophytic fungi Penicillium sp. YPT103-2 and Penicillium sp. YPT104 - Yu-Qin Yang; Jin-Feng Cao; Juan-Juan Pu; Dong-Ping Li; Chuan-Mao Zhang; Zhi-Jian Wu; Jian-Hai Ding (Natural Product Research, 2026)

In-situ monitoring reveals the determinants of dissolved methane concentrations within seagrass meadows in a lagoon in northern China - Rui Jin; Xiaoyong Duan; Ping Yin; Xue Li; Bin Chen; Ke Cao; Shenghua Lv; Daolai Zhang; Xingliang He; Xianguo Li; Dahai Zhang (Acta Oceanologica Sinica, 2026)

Structural and dynamic insights into SPDT for phosphorus allocation in rice - Haitao He; Yan Liu; Jie Zhang; Xiaofeng Zheng; Lihuan Jiang; Zhangmeng Du; Jiaqi Zuo; Shuo Cao; Xuemei Peng; Zhiwen Zheng; Kun Li; Cuicui Shen; et al. (Science China Life Sciences, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

First fossil fruit of Spatholobus (Papilionoideae, Fabaceae) from East Asia - Yi-Shan Zhao; Zhen-Dong Cao; Jing-Nan Huang; Zi-Yi Li; Torsten Wappler; Zhen-Xian Zhang; Shu-mei Xiao; Wei-Yu-Dong Deng; San-Ping Xie (Review of Palaeobotany and Palynology, 2026)

Sediment physicochemical and dissolved organic matter control microbial responses and nitrous oxide emissions across a coastal wetland transition from invasion to reclamation - Shengwei Cao; Yaci Liu; Ping Yang; Xiujian Hu; Yan Dong; Xiangyu Guan; Ping Yin; Yasong Li (Journal of Environmental Management, 2026)

Engineered Escherichia coli Nissle 1917 carrying D-lactate dehydrogenase suppresses glioblastoma malignancy via gut-brain axis reprogramming - Qun Cao; Jiazheng Wang; Xuxiu Lu; Zhuo Li; Chenghui Guo; Chuanke Hou; Ping Li; Anjing Chen (Chemical Engineering Journal, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

Photosensitive COFs-carboxylated nanocellulose membrane enables high-efficiency uranium extraction via synergistic coordination complexation and photocatalytic reduction - Shuaishuai Guo; Zhenlong Zeng; Dongyang Xu; Dingquan Li; Ping Cao; Jie Sun; Shiqin Zhang; Cheng Wang; Guowen Peng; Qingyi Zeng (Journal of Hazardous Materials, 2026)

In-situ construction of multi-site Co/Co-N-O porous carbons for plasma-catalytic toluene degradation - Chao Cao; Yixin Yang; Guangfei Qu; Rui Xu; Chenyang Zhao; Ping Ning; Junyan Li (Journal of Environmental Chemical Engineering, 2026)

The formation mechanism of ultra-deep gas condensate reservoirs: A case study of the Shunbei No. 4 strike-slip fault zone in the Tarim Basin, NW China - Xin Yang; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Jun Han; Feng Geng; Cheng Huang; Xinle Zhang; Zhongdeng Lu; Honghan Chen (Journal of Asian Earth Sciences, 2026)

Detrital record of multistage extension of the metamorphic core complex and arc tempos in the Jurassic Qiangtang Basin in central Tibetan Plateau - Ping Wang; Liang Duan; Lin Li; Chiyang Liu; Jianqiang Wang; Ronghao Wei; Xiaoyin Zhang; Jigang Cao (Global and Planetary Change, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Complete upcycling of iron phosphate slag via ammonium sulfide: Synchronous recovery of phosphorus, Fe7S8/C catalyst, and elemental sulfur - Shaoxiang Yang; Fei Zhang; Yikun Li; Fang Wang; Jiayu Feng; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Lijuan Jia (Chemical Engineering Journal, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Long-term no-tillage altered microbial communities and reduced C degradation while facilitating denitrification in a semi-arid cropland - Yuzheng Zong; Weifeng Wang; Wanhong Jin; Yinglan Chen; Shaohui Jia; Qian Liu; Yali Cao; Dongsheng Zhang; Xinrui Shi; Xingyu Hao; Ping Li (Applied Soil Ecology, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Anthropogenic heat amplification in industrial zones: Unraveling heat stress risk heterogeneity in river-sea dual-core cities - Yujie Li; Jingfu Cao; Mingcai Li; Song Jiang; Jie Yang; Rui Xin; Ping Qu; Jing Chen; Jing Wang (Sustainable Cities and Society, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

New Pachyportax fossils from the Late Miocene Shuitangba locality, Yunnan, revealing the early Bovini evolution and radiation - Ding-Ge Guo; Sayyed Ghyour Abbas; Qi-Gao Jiangzuo; Chun-Xiao Li; Yan-Wu Yang; Jia-Yong Cao; Bin Zou; Shi-Qi Wang; Xue-Ping Ji (Palaeoworld, 2026)

Process parameter optimization for greenhouse gas mitigation during green-waste composting and mechanistic insights from microbe–environment networks in treatments with contrasting outcomes - Xiaowen Li; Min Cao; Wenyuxin Huang; Hao Mei; Pan Luo; Ping Ma; Junhao Zhang; Weiqin Zhu; Miaomiao He; Ying Ding (Journal of Cleaner Production, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Study on the influencing factors of coaxial DBD plasma assisted coal combustion characteristics - Ping Li; Zhendong Cao; Haibo Hu; Deshan Wang; Haoyuan Song (Fuel, 2026)

Association between prenatal phthalate exposure and preschoolers’ blood pressure: Mediating role of DNA methylation in hypertension-related genes - Wei Wu; Zihao Wang; Wenwen Yang; Xiaoyuan Feng; Yifan Yang; Mengfei Xu; Beini Li; Ping Wu; Zhongqiang Cao (Environmental Pollution, 2026)

Spatial Variation in Grain Size of Riparian Dunes in Typical Cold and Arid Deserts of China and Its Implications for Identifying Sediment Sources - Xiaomei Li; Ping Yan; Liguo Cao; Xiaoxu Wang; Xiaokang Liu; Hao Chen (Chinese Geographical Science, 2026)

The effect of enrofloxacin exposure on energy metabolism and the ARGs transmission in grass carp: Potential contribution of microbiota-gut-liver axis - Ping Li; Bianhao Zeng; Xuqian Cao; Bin Liu; Ling Liu; Yi Chai; Zhi-Hua Li (Aquaculture, 2026)

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

A fluorescent probe based solid-state fluorophore for the detection of N2H4 and its application in environmental samples - Cong-Ping Cao; Qian Song; Chu-Yu-Hui Peng; Shuang-Xian Li; Guo-Jiang Mao; Juan Ouyang; Liufang Hu; Yongfei Li; Chun-Yan Li (Journal of Hazardous Materials, 2026)

Urbanization increases the impact of micropollutants on riverine planktonic food web - Bob Adyari; Lanping Zhang; Francisco J.A. Nascimento; Dandan Izabel-Shen; Yiqing Zhang; Meixian Cao; Jianjun Wang; Hongjun Li; Qian Sun; Chang-Ping Yu; Anyi Hu (Journal of Hazardous Materials, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

High-resolution mapping decouples hydrodynamic sorting and sediment transport as primary drivers of PAH distribution in the East China Sea inner shelf - Xiaoyong Duan; Ping Yin; Ke Cao; Fei Gao; Bin Chen; Meina Li; Shenghua Lv; Xiaoying Chen (Environmental Pollution, 2026)

Dual-dynamic polyimide and its thermally conductive adhesive featuring high glass transition temperature, recyclability, and strong adhesion - Fang Li; Ping Yu; Bin Wu; Ming Cao; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2026)

Mapping the spatial variability of hydrogen and oxygen isotopic compositions in Chinese lake water: Patterns and drivers - Hu Liu; Ping Zhang; Huanye Wang; Zhoufeng Wang; Zhonghui Liu; Meng Xing; Zheng Wang; Yixuan Li; Yunning Cao; Xiangzhong Li; Weiguo Liu (Science China Earth Sciences, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Synthetic peptide vaccines targeting SVA elicit robust protective immune responses in swine - Yamei Li; Nan Cao; Bo Yin; Mingfang Ji; Xiangzu Liu; Shudan Liu; Mingjin Jiao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

Toxic effects of enrofloxacin on grass carp (Ctenopharyngodon idellus): an ecological risk assessment based on cross-system regulatory mechanisms and network toxicology - Ping Li; Bianhao Zeng; Xuqian Cao; Yiwei Liu; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Yi Chai; Zhi-Hua Li (Aquatic Toxicology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Quantitative Evaluation of Gas Injection Contribution Using Fluid Inclusion Data: A Case Study of the Condensate Gas Reservoirs of the Eastern Shunbei Area in the Tarim Basin - Zicheng Cao; Lu Yun; Hongwei Ping; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Xin Yang; Honghan Chen (Journal of Earth Science, 2025)

Solar-activated ZnS@MXene heterostructure for integrated radioactive wastewater treatment and energy harvesting - Yi-Lin Liu; Ping Cao; Qingyan Zhang; Changgui Guo; Jing Li; Qingyi Zeng (Water Research, 2025)

Novel umami peptides from Grass Carp marinated with Red Yeast Rice Flour and their taste presentation mechanisms characterized by in silico approach and sensory evaluation - Qiaohui Zeng; Miaoshan Zhou; Lifang Gao; Ping Qi; Shilin Cao; Jian Li; Xinan Zeng; Jingjing Wang (Food Bioscience, 2025)

High-severity fire reduces soil erosion resistance: A study based on 4-year field monitoring data in dry-warm valley in Southwest China - Xiaosong Qin; Yi Wang; Longxi Cao; Ping Ren; Wei He; Yongkang Li; Dongdong Hou; Yufan Wang; Jia Xu (CATENA, 2025)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Polycyclic polyprenylated acylphloroglucinols with cytotoxicity against human tongue squamous carcinoma cells in vitro from Hypericum curvisepalum - Min-Min Cao; Xian Wei; Jie Huang; Zhong-Qiu Gan; Li-Ping Teng; Zhong-Bo Zhou (Phytochemistry Letters, 2025)

Quantifying the impact of thermal maturity on carbon isotope variations of marine oils from the Shunbei ultra-deep petroleum system, Tarim Basin - Zhongdeng Lu; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Honghan Chen (Organic Geochemistry, 2025)

Highly efficient and selective uranium capture across wide concentration and pH ranges by graphitic carbon nitride with multiple Lewis base sites - Wenxiu Sun; Minjie Wang; Qinyan Zhang; Ping Cao; Qingyun Yang; Mi Li; Tao Cai; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Oxidative damage induced by daily exposure to primary and emerging aromatic amines: Insights from large scale biomonitoring and cell-based high-throughput PCR array analysis - Shaohan Zhang; Zijun Zhou; Pingping Wang; Yanan Yao; Yuhao Cao; Jialan Liu; Ping Li; Tao Zhang; Hongkai Zhu; Lei Wang; Hongwen Sun; Zhipeng Cheng (Journal of Hazardous Materials, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Effect of blanching times and drying temperatures on the color, moisture migrations, microstructures, phytochemicals, and flavors of chili pepper (Capsicum annuum L.) - Yongkang Xie; Junjun Geng; Ping Li; Yan Zhao; Junhao Han; Hui Yang; Shina Cao (Food Chemistry, 2025)

Transcriptome and Metabolome Conjoint Analysis Revealed that PaGLK Affects Photosynthesis and Composition of Root Exudates in Poplar - Xiang-dong Bai; Yu Zheng; Li Cao; Wei Wang; Jing Jiang; Qi-bin Yu; Chuan-ping Yang; Gui-feng Liu (Plant Molecular Biology Reporter, 2025)

Deciphering dissolved inorganic carbon dynamics in Xiangshan Bay: isotopic constraints on sources, hydrodynamic controls, and anthropogenic influences - Xue Li; Xiaoyong Duan; Gang Tong; Ping Yin; Fei Gao; Ke Cao; Bin Chen (Acta Oceanologica Sinica, 2025)

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Unraveling the geochemical behaviors of rare earth elements (REEs) in Chinese drinking natural mineral waters: Environmental and health perspectives - Yifu Xu; Yuanchuan Li; Ping Wang; Chen Feng; Shiyu Cao; Jiangshan Li (Journal of Hazardous Materials, 2025)

AMF and biochar reshape the bacterial network in rhizosphere soil of Ricinus communis under chromium (Cr) stress and improve soil quality - Yuqiang Wen; Ruotong Wu; Tianle Xu; Ranran Cao; Ge Song; Dandan Qi; Wei Chang; Kun Li; Yuan Ping; Mengmeng Zhang; Xiaoxu Fan; Fuqiang Song (Journal of Hazardous Materials, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Impact of the Yangtze River on Sediment source-to-sink processes in estuarine bays: a study of the Oujiang River Estuary, SE China - Xia Guang; Ping Yin; Ke Cao; Fei Gao; Yuan Tian; Xiangtong Huang; Bin Chen; Meina Li; Jinqing Liu (Frontiers in Marine Science, 2025)
Our study was designed to unravel the provenance signals of sediments from various sediment source-to-sink processes. To achieve this, we systematically collected samples from river basins, estuaries, and offshore waters of the Oujiang River estuary. Analyses of clay minerals and trace geochemical elements (Cr, Th, Sc) were then conducted. Our findings revealed a dynamic pattern of sediment distribution, with the predominant clay minerals in the surface sediment of the offshore area being illite, followed by kaolinite and chlorite, with a minor smectite content. Notably, we observed a gradual increase in the proportions of illite and smectite from the upstream to the estuary, while kaolinite decreased accordingly. The ratios of Cr/Th and Sc/Th in the small mountain rivers also showed a gradual increase, indicating a rising influence of fine-grained sediment from the Yangtze River. Furthermore, we utilized a robust nonlinear mathematical model to determine and quantify the sources and provenance contributions of the clay fraction sediment in the Oujiang River estuary. Our model results revealed that the majority (64%) of the clay fraction sediment in the offshore region of the estuary originates from the Yangtze River. In contrast, sediments from small mountain rivers, including the Oujiang River, contribute an average of 29%, but this can increase to 40% within the Oujiang River estuary and its southern areas. Coastal currents and tides influence the sediment distribution in coastal areas. The Zhe-Min Coastal Current plays a significant role in transporting sediments from the Yangtze River to the estuaries of Zhejiang Province, where they settle in the downstream areas of the current. Moreover, sediment from the Oujiang River is carried southward by the coastal current, most of which is deposited in the estuary and the nearby coastal waters to the south. In conclusion, our study underscores the significant influence of sediments from the Yangtze River on the surface sediments in small mountain rivers and offshore regions near the Zhejiang coastline.

Understanding citrus aroma: Changes induced by postharvest treatments of fresh fruit - Shuxun Liu; Yuling Cai; Ying Lou; Yan Zhao; Mingfeng Cao; Ping Li; Qing Gu (Postharvest Biology and Technology, 2025)

Long-term effects of cropping regimes on soil organic carbon and aggregate stability in a Mollisol of Northeast China - Cuilan LI; Zhiyuan CAO; Mo ZHU; Hongjun GAO; Xiuzhi ZHANG; Ping ZHU; Jinjing ZHANG (Pedosphere, 2025)

The methane-sulfate transition interface in offshore sediments serves as a critical boundary for abrupt transitions in sedimentary environments - Xue Li; Xiaoyong Duan; Ping Yin; Ke Cao; Xingliang He; Jianghai Yang; Bin Chen (Marine and Petroleum Geology, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Using quantitative evaluation model to assess the environmental benefits of metabolites in flax retting wastewater aerobic compost: The trade-offs of core species build the profiles of beneficial and harmful metabolites converted from lignocellulose - Ying Yang; Zhichao Yang; Jie Kang; Zhenchao Wu; Yangcun Sun; Xinbo Cao; Yuhao Guo; Xiujun Tu; Liangyang Mao; Shuo Li; Weige Yao; Jingping Ge; et al. (Chemical Engineering Journal, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Agricultural practices influence phosphorus transport and ecosystem health in rice-paddy systems: Insights from HYDRUS-1D simulations - Shuoshuo Liang; Qingnan Chu; Ali Ashrafi; Zheng Zhao; Xiangyu Liu; Shuang Liu; Bei Yang; Detian Li; Ping He; Linkui Cao; Zhimin Sha; Chengrong Chen (Agriculture, Ecosystems & Environment, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Raman spectroscopy coupled with chemometrics for identification of adulteration and fraud in muscle foods: a review - Haiyang Ma; Jiajun Guo; Guishan Liu; Delang Xie; Bingbing Zhang; Xiaojun Li; Qian Zhang; Qingqing Cao; Xiaoxue Li; Fang Ma; Yang Li; Guoling Wan; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Identification and antidiabetic activity of peptides in protein Morus alba leaf proteolytic hydrolysates: A novel functional food ingredient for ameliorating type 2 diabetes mellitus - Ping Li; Tianli Cao; Zongshuo Li; Weidong Li (Food Bioscience, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Deciphering denitrification drivers in a high‑nitrogen estuary: Insights from stable isotope analysis and microbial molecular techniques - Shengwei Cao; Ping Yin; Chunlei Liu; Xiujian Hu; Yaci Liu; Yuewen Zhao; Xiangyu Guan; Yasong Li (Science of The Total Environment, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Genomic selection of resistance to acute hepatopancreatic necrosis disease in Litopenaeus vannamei - Mianyu Liu; Xupeng Li; Jie Kong; Xianhong Meng; Kun Luo; Juan Sui; Ping Dai; Jian Tan; Jiawang Cao; Baolong Chen; Hongjie Wang; Sheng Luan (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Greenhouse gas fluxes and their determining factors in salt marsh wetlands along the south shore of Hangzhou Bay, East China Sea - Fei Wang; Xiaoyong Duan; Gang Tong; Xue Li; Ke Cao; Xingliang He; Bin Chen; Fei Gao; Ping Yin; Xianguo Li; Dahai Zhang (Journal of Environmental Management, 2025)

Regulation of multilayer long crystalline MoS2 by NiO-modified Al2O3 for improved hydrodesulfurization of COS - Yubiao Li; Yu Liu; Xueqian Wang; Yixing Ma; Ping Ning; Langlang Wang; Xiang Li; Rui Cao (Environmental Research, 2025)

Biotransport and toxic effects of micro- and nanoplastics in fish model and their potential risk to humans: A review - Yanan Xu; Ling Liu; Yuqing Ma; Cunlong Wang; Fengshang Duan; Jianxue Feng; Haiyang Yin; Le Sun; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Aquatic Toxicology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The unity/diversity framework of executive functions: behavioral and neural evidence in older adults - Sheng-Ju Guo; Ping Wang; Li-Zhi Cao; Hui-Jie Li (GeroScience, 2025)

A novel blood spot with oil sealing for antioxidation and completeness preservation of erythrocytes and hemoglobin - Genhan Zha; Xuan Xiao; Youli Tian; Hengying Zhu; Qiang Zhang; Changjie Yu; Honggen Li; Yuxing Wang; Chengxi Cao; Ping Chen (Analytica Chimica Acta, 2025)

Miocene evolution of vegetation, climate, and elevation in the Wulan Basin of northeast Tibetan Plateau based on a CRACLE analysis of palynological assemblages - Xiao-Mei Li; Jia-Yi Chen; Zhen-Dong Cao; Li-Ming Liu; Si-Hang Zhang; Yun-Zhe Zhang; Li-Jie Wei; San-Ping Xie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Tectonic-climate-wildfire coupling during the Miocene in the northeastern Qinghai-Tibetan Plateau - Li-Ming Liu; Zhen-Dong Cao; Xiao-Mei Li; Si-Hang Zhang; Yun-Zhe Zhang; Jia-Yi Chen; De-Fei Yan; San-Ping Xie (Journal of Asian Earth Sciences, 2024)

Multi-omics analyses of the mechanism for formation of key aroma-active compounds in blood orange wine fermented by Pichia kudriavzevii - Shuxun Liu; Ying Lou; Yan Zhao; Yuling Cai; Mingfeng Cao; Yixian Li; Ping Li; Qing Gu (Food Research International, 2024)

Environmental behavior and toxic effects of micro(nano)plastics and engineered nanoparticles on marine organisms under ocean acidification: A review - Ling Liu; Haiyang Yin; Yanan Xu; Bin Liu; Yuqing Ma; Jianxue Feng; Zhihan Cao; Jinho Jung; Ping Li; Zhi-Hua Li (Environmental Research, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Accumulation of Prion Triggers the Enhanced Glycolysis via Activation of AMKP Pathway in Prion-Infected Rodent and Cell Models - Qin Fan; Kang Xiao; Ruhan A; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Chao Hu; Xiao-Xi Jia; Chu-Mou Liu; Xin Liu; Cao Chen; Qi Shi; et al. (Molecular Neurobiology, 2024)

Microcolumn and coelution hydration of oil seal blood spot for efficient screening of newborn α-thalassemia via chip isoelectric focusing - Genhan Zha; Xuan Xiao; Youli Tian; Hengying Zhu; Ping Chen; Qiang Zhang; Changjie Yu; Honggen Li; Yuxing Wang; Chengxi Cao (Analytica Chimica Acta, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Polymorphisms of PRKAA1 and FABP4 genes and their association with feed efficiency in Hu sheep - Mengru Pu; Deyin Zhang; Liming Zhao; Dan Xu; Zongwu Ma; Kunchao Han; Lijuan He; Chengqi Yan; Qi Zhang; Lianjun Feng; Ziyue Xiao; Lei Gao; et al. (Small Ruminant Research, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Conjugation-regulated lateral and stereoelectronic effects in single-molecule junctions - Xiao Wei; Xuanhao Cao; Jie Hao; Xinyue Chang; Ping Duan; Li Cheng; Keqiu Chen; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Chemical Engineering Journal, 2024)

Construction of La/Al2O3 nanorod-like catalyst with rich basic sites: Enabling efficient conversion of COS-superior selectivity and theoretical insights - Rui Cao; Xueqian Wang; Langlang Wang; Fangxian Cao; Xiang Li; Lu Wang; Jinghao Xiang; Ping Ning (Chemical Engineering Journal, 2024)

Holocene aeolian environmental dynamics in fixed and semi-fixed deserts over the arid Central Asia revealed by comprehensive sand-dune records - Min Cao; Ping Lü; Fang Ma; Linhai Yang; Junlin Yu; Zishu Xia; Chao Li (CATENA, 2024)

Aberrant Enhanced NLRP3 Inflammasomes and Cell Pyroptosis in the Brains of Prion-Infected Rodent Models Are Largely Associated with the Proliferative Astrocytes - Dong-Hua Zhou; Xiao-Xi Jia; Yue-Zhang Wu; Wei-Wei Zhang; Yuan Wang; Dong-Lin Liang; Li-Ping Gao; Kang Xiao; Cao Chen; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2024)

Vitamin D receptor attenuates carbon tetrachloride-induced liver fibrosis via downregulation of YAP - Ping Wang; Jie Li; Mintao Ji; Jinjing Pan; Yanmei Cao; Yulin Kong; Li Zhu; Jiafu Li; Bingyan Li; Lei Chang; Zengli Zhang (Journal of Hazardous Materials, 2024)

Controlled dispersion and morphology in MoS2/SBA-15 catalysts for enhanced COS hydrodesulfurization - Li Yubiao; Cao Rui; Liu Yu; Wang Langlang; Ning Ping; Wang Xueqian; Ma Yixing (Fuel, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

A nanoparticle vaccine based on the VP121–26 and VP2 structural proteins of Senecavirus A induces robust protective immune responses - Nan Cao; Yamei Li; Huawei Zhang; Xiangzu Liu; Shudan Liu; Mingxing Lu; Zihui Hu; Linxing Tian; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2024)

A citrullinated antigenic vaccine in treatment of autoimmune arthritis - Xu Jin; Tianya Dong; Qian Wang; Yang Xie; Xiangyu Fang; Chaonan Wei; Shuyan Liu; Xi Zheng; Ping Wang; Danxue Zhu; Lulu Cao; Suwei Dong; et al. (Science Bulletin, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

T Cells Trafficking into the Brain in Aging and Alzheimer’s Disease - Yue-Zhang Ma; Jia-Xin Cao; Yi-Shu Zhang; Xiao-Mei Su; Yu-Hong Jing; Li-Ping Gao (Journal of Neuroimmune Pharmacology, 2024)

Garciyunnanones A–R: Caged polycyclic polyprenylated acylphloroglucinols decorated with a lavandulyl substituent from Garcinia yunnanensis - Miaomiao Nan; Yueyou Yang; Ping Ying; Qiang Zheng; Youjun Wu; Tianjie Cao; Ting Li; Weiming Huang; Chuanlu Fu; Lingyi Kong; Wenjun Xu (Phytochemistry, 2024)

Modulating proportion of Ni0 species stabilized by Ni2+ on Ni-MgO catalyst with superior stability for dry reforming of methane - Xieyi Liu; Junjie Wen; Yu xie; Zongling Li; Manshu Zhong; Rongbing Nie; Shiyuan Peng; Jinyan Cao; Jianjun Chen; Ping Ning; Qiulin Zhang (Chemical Engineering Journal, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Comparison of Drought Stress Responses in Large- and Small-Rooted Rice Lines: Physiological, Anatomical, and Hormonal Changes - Yao Guo; Yunfeng Du; Xinze Niu; Yunjing Ma; Guoqing Song; Cougui Cao; Ping Li; Yinglong Chen; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2024)

Recent progress and perspectives on coal dust sources, transport, hazards, and controls in underground mines - Yong Cao; Yang Xiao; Zhen-Ping Wang; Qing-Wei Li; Chi-Min Shu; Xing-Rui Jiang; Shi-Liang Wu (Process Safety and Environmental Protection, 2024)

Dynamic modulation of nodulation factor receptor levels by phosphorylation-mediated functional switch of a RING-type E3 ligase during legume nodulation - Hao Li; Yajuan Ou; Jidan Zhang; Kui Huang; Ping Wu; Xiaoli Guo; Hui Zhu; Yangrong Cao (Molecular Plant, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Exploring the Impact of Biodegradable and Nonbiodegradable Microplastic Particles on Pb Absorption in Maize - Dan QIU; Chunmiao LU; Huarong SUN; Chaohang LI; Guangqiang LONG; Ping ZHAO; Yijun LONG; Yue DING; Cuixia SU; Zhengyan PAN; Yuefang CAO; Shuran HE (Journal of Soils and Sediments, 2024)

Microstrip isoelectric focusing with deep learning for simultaneous screening of diabetes, anemia, and thalassemia - Haodong Fu; Youli Tian; Genhan Zha; Xuan Xiao; Hengying Zhu; Qiang Zhang; Changjie Yu; Wei Sun; Chang Ming Li; Li Wei; Ping Chen; Chengxi Cao (Analytica Chimica Acta, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

P53 upregulation by USP7-engaging molecular glues - Zhaoyang Li; Ziying Wang; Chao Zhong; Hang Zhang; Rui Liu; Ping An; Zhiqiang Ma; Junmei Lu; Chengfang Pan; Zhaolin Zhang; Zhiyuan Cao; Jianyi Hu; et al. (Science Bulletin, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

A New Perspective on the Semi-quantitative Meso-structural Failure Mechanism of Deep Weak Interlayer Zone Under Different Stress Paths - Shu-Qian Duan; Po Gao; Ding-Ping Xu; Bei Cao; Guo-feng Liu; Quan Jiang; Shi-Li Qiu; Jie-Cheng Xiong (Rock Mechanics and Rock Engineering, 2024)

Electrokinetic bioremediation of trichloroethylene and Cr/As co-contaminated soils with elevated sulfate - Qizheng Cai; Chongwen Shi; Zixuan Cao; Zhengtao Li; He-Ping Zhao; Songhu Yuan (Journal of Hazardous Materials, 2024)

Mechanism and effectiveness of enzymatically induced phosphate precipitation (EIPP) in stabilizing coexisting lead, zinc, and cadmium in tailings - Lijun Han; Ping Wang; Xiqing Jiang; Yaoyi Wang; Shiyu Cao; Jiangshan Li (Environmental Pollution, 2024)

Seasonal variations and size-dependent distribution of heavy metals in particulate matter in Huangshi: Implications for human health risk assessment - Yuhu Xie; Yao Mao; Ping Zhong; Yong Zhang; Li Zhang; Wei Chen; Chengkai Qu; Xinli Xing; Junji Cao; Jiaquan Zhang (Atmospheric Environment, 2024)

Review on recent advances of Gracilariopsis lemaneiformis (Rhodophyta) - Mengxing Cao; Jingyu Zhang; Pingping Li; Jinguo Wang; Ping Mi; Zhenghong Sui (Algal Research, 2024)

The relationships between vertical variations of shallow gas and pore water geochemical characteristics in boreholes from the inner shelf of the East China Sea - Xue Li; Xiaoyong Duan; Xingliang He; Yongqing Xie; Lei Yang; Ping Yin; Ke Cao; Bin Chen; Fei Gao; Feng Li (Frontiers in Marine Science, 2024)
Shallow gas was widely recognized in the coastal region, especially in the estuarine delta areas with high organic matter (OM) burial flux. In this study, the vertical variations of shallow gas and the related geochemical indicators from two boreholes in the coastal region of the East China Sea (ECS) were investigated. Two gas-bearing layers were identified in the sediments from the Holocene and late Pleistocene series. Both boreholes exhibit a “typical” and an “inverse” Sulfate Methane Transition Zone (SMTZ). The “typical” SMTZs (SMTZ1 and SMTZ3) were in the upper part of the gas-bearing layers, where sulfate levels decrease and methane levels increase with depth. Conversely, the “inverse” SMTZs (SMTZ2 and SMTZ4) were in the lower part of the gas-bearing layers, exhibiting an increase in sulfate levels and a decrease in methane levels with depth, a phenomenon rarely documented in previous research. The downward variations of pore water geochemical characteristics indicates that these ions were related to Anaerobic Oxidation of Methane (AOM) processes. The increase in Ca 2+ and Ba 2+ concentrations and the gradual decrease in sulfate at the SMTZ reflect a series of biogeochemical processes resulting from the dissolution of carbonate and other minerals by AOM. The research indicates that sulfate in AOM may originate from multiple sources. Through analyzing the vertical distribution of shallow gas and the geochemical properties of pore water, this study elucidates the shallow gas formation mechanism and the features of the SMTZ, laying the groundwork for further investigations.

Induced Mesenchymal Stem Cells-Small Extracellular Vesicles Alleviate Post-stroke Cognitive Impairment by Rejuvenating Senescence of Neural Stem Cells - Jiayuan Liu; Li Peng; Lingwei He; Tianyue Yin; Yuhao Du; Mengmeng Yang; Ping Wu; Jun Li; Jiangbing Cao; Hongrui Zhu; Sheng Wang (Journal of Molecular Neuroscience, 2024)

Evolution of groundwater hydrochemical characteristics and formation mechanism during groundwater recharge: A case study in the Hutuo River alluvial–pluvial fan, North China Plain - Ping Wang; Wei Zhang; Yuchen Zhu; Yaci Liu; Yasong Li; Shengwei Cao; Qichen Hao; Shenghua Liu; Xiangke Kong; Zhantao Han; Binghua Li (Science of The Total Environment, 2024)

Microbial colony sequencing combined with metabolomics revealed the effects of chronic hexavalent chromium and nickel combined exposure on intestinal inflammation in mice - Yueming Gu; Shuangyan Zheng; Cheng Huang; Xianhong Cao; Ping Liu; Yu Zhuang; Guyue Li; Guoliang Hu; Xiaona Gao; Xiaoquan Guo (Science of The Total Environment, 2024)

Miocene Equisetum tubers from the Wulan Basin, Northeast Qinghai-Tibetan Plateau and their paleoecological significance - Zhen-Dong Cao; Peng Zhang; Si-Hang Zhang; Yi-Hong Yang; Jia-Yi Chen; Li-Ming Liu; Xiang-Chuan Li; San-Ping Xie (Palaeoworld, 2024)

Quantitative characterization of resident’ exposure to typical semi-volatile organic compounds (SVOCs) around a non-ferrous metal smelting plant - Mengmeng Wang; Yiyi Li; Yinyi Lv; Jian Tang; Pengkun Wei; Ping Lu; Leicheng Zhao; Guiying Li; Zhiguo Cao; Taicheng An (Journal of Hazardous Materials, 2024)

Evaluation of therapeutic benefits of botulinum toxin for foot dystonia associated with Parkinson's disease - Ping Ni; Ying-ying Xu; Lin-na Wang; Jia-qian Cao; Wei-feng Luo; Qi-lin Zhang; Xiang Li; Xu-ping Zhou; Jing Liu (Toxicon, 2024)

Environmentally persistent free radicals on photoaged microplastics from disposable plastic cups induce the oxidative stress-associated toxicity - Hanlin Cao; Ping Ding; Xintong Li; Chushan Huang; Xin Li; Xiaoxia Chen; Lijuan Zhang; Jianying Qi (Journal of Hazardous Materials, 2024)

Biodegradation properties and mechanism of triketone herbicide mesotrione via newly isolated bacterium Klebsiella pasteurii CM-1 - Xiaotian Cao; Yuanfu Li; Wei Liu; Ning Hou; Feng Zhao; Ping Han; Huihua Tan (International Biodeterioration & Biodegradation, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Economy and carbon emissions optimization of different provinces or regions in China using an improved temporal attention mechanism based on gate recurrent unit - Lian Cao; Yongming Han; Mingfei Feng; Zhiqiang Geng; Yi Lu; Liangchao Chen; Weiying Ping; Tao Xia; Shaobo Li (Journal of Cleaner Production, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Genetic spectrums and clinical profiles of critically ill neonates with congenital auricular deformity in the China Neonatal Genomes Project - Feifan Xiao; Bingbing Wu; Chenbin Dong; Guoqiang Cheng; Yun Cao; Laishuan Wang; Xinran Dong; Yulan Lu; Lin Yang; Liping Chen; Long Li; Xinnian Pan; et al. (Human Genetics, 2023)

Precipitation regulated soil nematode community and footprint in cropland ecosystems - Pingting Guan; Jianan Li; Cao Hao; Jingjing Yang; Lihong Song; Ximei Niu; Ping Wang; Mohammad Mahamood; Donghui Wu (Soil Ecology Letters, 2023)

Establishment and characterization of a novel hilar cholangiocarcinoma cell line, CBC3T-1 - Mingzhen Bai; Ningzu Jiang; Wenkang Fu; Chongfei Huang; Liang Tian; Ningning Mi; Long Gao; Haidong Ma; Yawen Lu; Jie Cao; Chao Zhang; Ping Yue; et al. (Human Cell, 2023)
Cholangiocarcinoma (CCA) is a group of malignant heterogeneous cancer arising from the biliary tree. The tumor is characterized by insidious onset, high degree of malignancy, poor prognosis, and high recurrence rate. Immortalized cancer cell lines are the best and easiest models for in vitro cancer research. Here, we established a naturally immortalized highly tumorigenic hilar cholangiocarcinoma (hCCA) cell line, CBC3T-1. The CBC3T-1 cell line was cultured for over 60 passages. Thorough analysis showed that CBC3T-1 cells share characteristics similar to original tumor cells from patients with cholangiocarcinoma and display a stable phenotype, including features of epithelial origin, stem cell-like properties, as well as a high invasive and migratory capability and tumorigenicity in mice. Furthermore, this cell line showed the best sensitivity to paclitaxel, followed by gemcitabine. RNA sequencing and whole‑exome sequencing showed that cancer-associated pathways and somatic mutations played a dominant role in the development of CCA. We established and characterized a new hCCA cell line, CBC3T-1, which contributes to a better understanding of bile duct cancer, and can be used to study tumorigenesis and progression and the role of anticancer drugs.

Biomass-derived carbon dots with light conversion and nutrient provisioning capabilities facilitate plant photosynthesis - Bingxu Cheng; Zhilin Yang; Feiran Chen; Le Yue; Xuesong Cao; Jing Li; Hai-Long Qian; Xiu-Ping Yan; Chuanxi Wang; Zhenyu Wang (Science of The Total Environment, 2023)

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Metabolomics reveals the effects of different storage times on the acidity quality and metabolites of large-leaf black tea - Suwan Zhang; Qiuhua Li; Shuai Wen; Lingli Sun; Ruohong Chen; Zhenbiao Zhang; Junxi Cao; Zhaoxiang Lai; Zhigang Li; Xingfei Lai; Ping Wu; Shili Sun; et al. (Food Chemistry, 2023)

High starch diets attenuate the immune function of Micropterus salmoides immune organs by modulating Keap1/Nrf2 and MAPK signaling pathways - Hongli Liu; Baipeng Chen; Yanhao Cao; Yi Geng; Ping Ouyang; Defang Chen; Liangyu Li; Xiaoli Huang (Fish & Shellfish Immunology, 2023)

Nitrogen removal performances and metabolic mechanisms of denitrification systems using different volatile fatty acids as external carbon sources - Xin Li; Xiangzhen Li; Chaonan Li; Na Li; Ping Zou; Xiaolong Gao; Qin Cao (Chemical Engineering Journal, 2023)

Spotlight on Pt/γ-Al2O3 with high catalytic performance induced by Barium: Synergistic effect of electron-rich Ptδ- single-atoms and available oxygen species - Jianjun Chen; Huiling Weng; Zhiyu Li; Rongbing Nie; Jinyan Cao; Qiulin Zhang; Ping Ning; Yaoqiang Chen; Jiming Hao (Chemical Engineering Journal, 2023)

The Epidemiology of Tinea Capitis in Guangxi Province, China - Dongyan Zheng; Tianwei Liang; Weixuan Wu; Najwa Al-Odaini; Kaisu Pan; Lan Huang; Guomei Huang; Lulu Tang; Xinlei Li; Shao He; Huahui Jian; Nibo Wei; et al. (Mycopathologia, 2023)

A self-assembled nanoparticle vaccine based on pseudorabies virus glycoprotein D induces potent protective immunity against pseudorabies virus infection - Xujiao Ren; Nan Cao; Linxing Tian; Wenqiang Liu; Hechao Zhu; Zhenxiang Rong; Manman Yao; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2023)

Effects of insulin-like growth factor 1, leukemia inhibitory factor, and basic fibroblast growth factor on goat oocyte maturation and early embryonic development in vitro - Zhao Gao-Ping; Shi Pei-Xin; Chang Qing; Wang Zi-Xin; Li Yun-Xia; Zhao Li-Xia; Sun Wei; Wu Meng; Bao Si-Qin; Cao Gui-Fang; Li Xi-He (Small Ruminant Research, 2023)

COS and H2S simultaneous removal from blast furnace gas over a tailored Cu/Zr co-doped K@TiO2 bifunctional catalyst under low temperature - Xiang Li; Xueqian Wang; Li Yuan; Langlang Wang; Yixing Ma; You Wu; Yibing Xie; Rui Cao; Yiran Xiong; Ping Ning (Chemical Engineering Journal, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Evaluation of Physiological Stress of Grass Carp Chronically Exposed to Enrofloxacin Based on IBR Index - Xu-Qian Cao; Xu Wang; Bin Liu; Shu-Wen He; Zhi-Han Cao; Shao-Ying Xing; Ping Li; Zhi-Hua Li (Water, Air, & Soil Pollution, 2023)

Fatigue fracture behaviour and constitutive model of freeze-thaw sandstone under multilevel fatigue loads - Zhanming Shi; Jiangteng Li; Mengxiang Wang; Jinci Chen; Hang Lin; Ping Cao (Bulletin of Engineering Geology and the Environment, 2023)

Resveratrol and Sir2 Reverse Sleep and Memory Defects Induced by Amyloid Precursor Protein - Yuping Hao; Lingzhan Shao; Jianan Hou; Yan Zhang; Yuqian Ma; Jinhao Liu; Chuan Xu; Fujun Chen; Li-Hui Cao; Yong Ping (Neuroscience Bulletin, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Salinity variations of the inner Yangtze Sea during the Ordovician-Silurian transition and its influences on marginal marine euxinia - Guangyao Cao; Yu Liu; Chao Li; Ping'an Peng; Mingcai Hou; Gary G. Lash; Xiaolin Zhou; Yuanchun Li; Ying Song (Global and Planetary Change, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

Numerical simulation of the electromagnetic field in layered media applicable to high-frequency scenarios - Kun Li; Xu-Ri Huang; Kang Chen; Yun-Gui Xu; Wei-Ping Cao (Applied Geophysics, 2023)

Physical activity mitigates the influence of blood cadmium on memory function: a cross-sectional analysis in US elderly population - Yanwei You; Yuquan Chen; Jinwei Li; Qi Zhang; Yang Zhang; Ping Yang; Qiang Cao (Environmental Science and Pollution Research, 2023)

Multi-scale structure characterization of ozone oxidized waxy rice starch - Jing Li; Meng Du; Zia-ud Din; Ping Xu; Lei Chen; Xi Chen; Yuehui Wang; Yang Cao; Kun Zhuang; Jie Cai; Qingyun Lyu; Xianhui Chang; et al. (Carbohydrate Polymers, 2023)

Novel function of a putative TaCOBL ortholog associated with cold response - Fang-Fang Liu; Ying-Xiu Wan; Wen-Xin Cao; Qi-Qi Zhang; Yao Li; Yan Li; Ping-Zhi Zhang; Hong-Qi Si (Molecular Biology Reports, 2023)

Single-cell transcriptomic analysis reveals the developmental trajectory and transcriptional regulatory networks of pigment glands in Gossypium bickii - Yue Sun; Yifei Han; Kuang Sheng; Ping Yang; Yuefen Cao; Huazu Li; Qian-Hao Zhu; Jinhong Chen; Shuijin Zhu; Tianlun Zhao (Molecular Plant, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Systematic toxicological analysis of the effect of salinity on the physiological stress induced by triphenyltin in Nile tilapia - Zhi-Hua Li; Shaoying Xing; Ping Li; Shuwen He; Zhihan Cao; Xu Wang; Xuqian Cao; Bin Liu; Hong You (Aquatic Toxicology, 2023)

Interactions between Cr(VI) and the hydrochar: The electron transfer routes, adsorption mechanisms, and the accelerating effects of wood vinegar - Zirui Wang; Nan Lu; Xu Cao; Qingzi Li; Shangyu Gong; Ping Lu; Ke Zhu; Jiunian Guan; Til Feike (Science of The Total Environment, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Distribution, sources and health risks of heavy metals in indoor dust across China - Mengmeng Wang; Yinyi Lv; Xinyan Lv; Qianhan Wang; Yiyi Li; Ping Lu; Hao Yu; Pengkun Wei; Zhiguo Cao; Taicheng An (Chemosphere, 2023)

Assessing the ecotoxicity of combined exposure to triphenyltin and norfloxacin at environmental levels: A case study of immunotoxicity and metabolic regulation in carp (Cyprinus carpio) - Si-Qi Zhang; Ping Li; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Xue-Li Zhao; Cuici Sun; Zhi-Hua Li (Chemosphere, 2023)

Aggregation-induced emission luminogens-encoded microspheres preparation and flow-through immunoaffinity chromatographic assay development for microcystin-LR analysis - Peng Zhai; Chen Liu; Gang Feng; Yuanhao Cao; Lei Xiang; Keshi Zhou; Ping Guo; Jianqing Li; Wenxiao Jiang (Food Chemistry, 2023)

Effects of bepridil on early cardiac development of zebrafish - Ya-Lan Wei; Yu-Qing Lei; Zhou-Jie Ye; Xu-Dong Zhuang; Li-Ping Zhu; Xin-Rui Wang; Hua Cao (Cell and Tissue Research, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Regulating electronic structure by Mn doping for nickel cobalt hydroxide nanosheets/carbon nanotube to promote oxygen evolution reaction and oxidation of urea and hydrazine - Kaili Wu; Chenyang Cao; Keren Li; Chaojie Lyu; Jiarun Cheng; Hongyu Li; Pengfei Hu; Jiwen Wu; Woon-Ming Lau; Xixi Zhu; Ping Qian; Jinlong Zheng (Chemical Engineering Journal, 2023)

Knockdown of lncRNA-ASLNC12002 alleviates epithelial–mesenchymal transition of type II alveolar epithelial cells in sepsis-induced acute respiratory distress syndrome - Kaixuan Feng; Weifeng Huang; Jiawei Shang; Feng Ping; Qin Tan; Wei Wang; Yingchuan Li; Yongmei Cao (Human Cell, 2022)
Patients with sepsis-induced acute respiratory distress syndrome (ARDS) have higher mortality and poor prognosis than pneumonia-induced ARDS. Pulmonary fibrosis is an irreversible accumulation of connective tissue in the interstitium of the lung and closely associated with the epithelial–mesenchymal transition (EMT) of type II alveolar epithelial cells (AECIIs). Therefore, it is undoubtedly worth studying whether the EMT of AECIIs in sepsis-induced ARDS patients is different from that in patients with pneumonia-induced ARDS in the regulatory mechanism. Here, we will report for the first time that an lncRNA-ASLNC12002 is highly expressed in AECIIs of patients with sepsis-induced pneumonia and promotes EMT in AECIIs. The research results showed that the expression of ASLNC12002 in AECIIs derived from patients with sepsis-induced ARDS is significantly higher than that in normal people and pneumonia-induced ARDS patients. Mechanism research showed that ASLNC12002 can cause the inactivation of the anti-EMT pathway NR2F2/miR128-3p/Snail1 by acting as the sponge of miR128-3p. Functional experiments showed that targeted silencing of ASLNC12002 could effectively inhibit EMT progression in AECIIs of patients with sepsis-induced pneumonia by restoring NR2F2/miR128-3p/Snail1 pathway. In a word, our study shows for the first time that the inactivation of NR2F2/miR128-3p/Snail1 pathway caused by the enhanced expression of ASLNC12002 is the direct reason why AECIIs in sepsis-induced ARDS patients are prone to get EMT progress. ASLNC12002 has the potential to become a biological target for the prevention and treatment of pulmonary fibrosis in patients with sepsis-induced ARDS. At the same time, the expectation that ASLNC12002 and its related products may be used as clinical markers for the evaluation of early pulmonary fibrosis in ARDS patients should not be ignored.

Acute Toxicity of a Novel anti-fouling Material Additive DCOIT to Marine Chlorella sp - Jin-Chuang Ru; Xue-Li Zhao; Zhi-Han Cao; Cheng-Zhuang Chen; Ping Li; Zhi-Hua Li (Bulletin of Environmental Contamination and Toxicology, 2022)

An hourly shallow landslide warning model developed by combining automatic landslide spatial susceptibility and temporal rainfall threshold predictions - Yi-ming Cao; Wei Guo; Yu-ming Wu; Lang-ping Li; Yi-xing Zhang; Heng-xing Lan (Journal of Mountain Science, 2022)

Physiological responses of marine Chlorella sp. exposed to environmental levels of triphenyltin - Zhihan Cao; Ping Li; Jinchuang Ru; Xuqian Cao; Xu Wang; Bin Liu; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Enhanced M-CSF/CSF1R Signaling Closely Associates with PrPSc Accumulation in the Scrapie-Infected Cell Line and the Brains of Scrapie-Infected Experimental Rodents - Ying Xia; Cao Chen; Jia Chen; Chao Hu; Wei Yang; Lin Wang; Lian Liu; Li-Ping Gao; Yue-Zhang Wu; Dong-Dong Chen; Qi Shi; Zhi-Bao Chen; et al. (Molecular Neurobiology, 2022)

Correction to: Physiological Mechanism of Drought-Resistant Rice Coping With Drought Stress - Benfu Wang; Xiaolong Yang; Liang Chen; Yuanyuan Jiang; Hongying Bu; Yang Jiang; Ping Li; Cougui Cao (Journal of Plant Growth Regulation, 2022)

Physiological Mechanism of Drought-Resistant Rice Coping With Drought Stress - Benfu Wang; Xiaolong Yang; Liang Chen; Yuanyuan Jiang; Hongying Bu; Yang Jiang; Ping Li; Cougui Cao (Journal of Plant Growth Regulation, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

Differential expression and functional analysis of circRNA in the ovaries of Yili geese at different egg-laying stages - Xiao-yu Zhao; Ying-ping Wu; Hai-ying Li; Yan Cao; Zhi-yong Mei; Jia-hui Li (Genes & Genomics, 2022)

Genetic Control of the Root System Traits in Oilseed Rape Under Contrasting Phosphate Supply Conditions by Genome-wide Association Study - Ping Xu; Xiaohua Wang; Hui Li; Shengjie Dai; Xue Cao; Zhenning Liu (Plant Molecular Biology Reporter, 2022)

Bio-organic Fertilizer with Bacillus subtilis F2 Promotes Strawberry Plant Growth and Changes Rhizosphere Microbial Community - Li Liu; Xiang Li; Tianyu Li; Yuan Xie; Zhuoyang Cao; Ping Fang (Journal of Soil Science and Plant Nutrition, 2022)

Effects of long-term exposure of norfloxacin on the HPG and HPT axes in juvenile common carp - Si-Qi Zhang; Xue-Li Zhao; Shu-Wen He; Shao-Ying Xing; Zhi-Han Cao; Ping Li; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

Expanding the clinical spectrum of adult-onset neuronal intranuclear inclusion disease - Yuwen Cao; Jingying Wu; Yunhua Yue; Chao Zhang; Shihua Liu; Ping Zhong; Shige Wang; Xiaojun Huang; Weiping Deng; Jing Pan; Lan Zheng; Qing Liu; et al. (Acta Neurologica Belgica, 2022)

Potential Application of Biosurfactant-Producing Bacteria for Bioremediation of Oil Polluted Marine Intertidal Sediments - Ping Guo; Wei-Wei Xu; Dan-Na Wei; Man-Xia Zhang; Jin Zhang; Shi Tang; Bin-Xia Cao; Jian-Guo Lin; Wei Li (Journal of Marine Science and Engineering, 2022)
The removal of oil contaminants in marine intertidal sediments under cold climate is an urgent issue. Although the bioavailability of petroleum hydrocarbons decreases at low temperatures, biosurfactants can promote oil biodegradation. In this study, characteristics of biosurfactants produced by cold-adapted oil-degrading bacteria Planococcus sp. XW-1 were studied. Adding the XW-1 biosurfactant could effectively facilitate the solubility of phenanthrene, pyrene, diesel oil, and crude oil. The solubilization was limited by the number of rings and the molecular weight (WSRphenanthrene = 0.0234; WSRpyrene = 0.0165; WSRdiesel oil = 0.0027; WSRcrude oil = 0.0015). Additional biosurfactants significantly washed out crude oil adsorbed to the sand (reduction from 17.1%, 22.7% to 87.9% and 94.28% in 24 h). With the increase in particle size, the removal efficiency increased from 87.9% to 94.28%. After the addition of biosurfactant, the effect of degradation increased by 20% in 20 days. The results suggest that the biosurfactant-producing bacteria Planococcus sp. XW-1 is a promising candidate used in the in situ bioremediation of petroleum-contaminated intertidal sediment.

Citrus flavonoids and their antioxidant evaluation - Yue Wang; Xiao-Juan Liu; Jie-Biao Chen; Jin-Ping Cao; Xian Li; Chong-De Sun (Critical Reviews in Food Science and Nutrition, 2022)

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Long-Term Ammonia Toxicity in the Hepatopancreas of Swimming Crab Portunus trituberculatus: Cellular Stress Response and Tissue Damage - Yunliang Lu; Jingyan Zhang; Jianwei Cao; Ping Liu; Jian Li; Xianliang Meng (Frontiers in Marine Science, 2022)
Ammonia is the most common contaminant in aquaculture systems. Due to the unexpected deterioration of natural seawater quality caused by harmful alga blooms in summer, the water exchange cycle for the culture ponds of the swimming crab Portunus trituberculatus , an important aquaculture species in China, is often much longer, and the crabs may be exposed to long-term ammonia stress. However, less information is available regarding the long-term effects of ammonia in marine decapod crustaceans. Therefore, it is of great significance to understand the toxic effects of prolonged ammonia in decapods. In this study, alteration of histology, cellular stress responses (CSRs), and apoptosis in the hepatopancreas of P. trituberculatus , an important aquaculture species, during ammonia stress (5, 15, and 45 mg⋅L –1 ) for 1, 7, and 15 days and recovery at the normal condition for 7 days, were analyzed. Our results demonstrated a serious impact of long-term (15 days) ammonia stress by depressing crab CSR especially when ammonia concentration exceeds 15 mg⋅L –1 . Overall, short- (1 day) and medium-term (7 days) ammonia stress induced CSR, evidenced by upregulated expression of the genes involved in antioxidant defense ( SOD , CAT , and GPX ), apoptosis ( p53 , Bax , and Caspase-3 ), heat shock response (HSR) ( Hsp70 and Hsp90 ), unfolded protein response (UPR) ( IRE1 , ATF6 , and XBP1 ), and DNA damage response (DDR) ( ATR and DNA-PKcs ). However, long-term (15 days) ammonia stress, especially when exposed to the ammonia of 15 and 45 mg⋅L –1 , resulted in a higher level of apoptosis and severe damage of hepatopancreas, which may be related to the depressed CSR including antioxidant defense, HSR, UPR, and DDR. Notably, after recovery, the expressions of many genes involved in apoptosis, antioxidant response, HSR, UPR, and DDR in the groups exposed to ammonia at 15 and 45 mg⋅L –1 were still significantly different to that of the control group. In summary, care should be taken when P. trituberculatus is exposed to ammonia over 15 mg⋅L –1 especially when exposure duration is longer than 15 days, as the CSR could be compromised. This study provides a reference for a comprehensive understanding of CSR in decapod crustaceans under ammonia stress and will be beneficial for management in the intensive culture of the swimming crab.

Fracture analysis of central-flawed rock-like specimens under the influence of coplanar or non-coplanar edge flaws - Zhizhen Liu; Ping Cao; Kaihui Li; Fei Wang; Tao Dong; Jingshuo Liu (Bulletin of Engineering Geology and the Environment, 2022)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

Distinct Aeolian-fluvial Interbedded Landscapes in Three Watersheds of the Northern China - Xiaomei Li; Ping Yan; Liguo Cao; Baoli Liu (Chinese Geographical Science, 2021)

Genetic Prion Disease: Insight from the Features and Experience of China National Surveillance for Creutzfeldt-Jakob Disease - Qi Shi; Cao Chen; Kang Xiao; Wei Zhou; Li-Ping Gao; Dong-Dong Chen; Yue-Zhang Wu; Yuan Wang; Chao Hu; Chen Gao; Xiao-Ping Dong (Neuroscience Bulletin, 2021)

A latest review on the application of microcosm model in environmental research - Zhihan Cao; Ping Li; Zhi-Hua Li (Environmental Science and Pollution Research, 2021)

Globular adiponectin inhibits osteoblastic differentiation of vascular smooth muscle cells through the PI3K/AKT and Wnt/β-catenin pathway - Yun Zhou; Li-Long Wei; Rui-Ping Zhang; Cheng-Wu Han; Yongtong Cao (Journal of Molecular Histology, 2021)
Lipid metabolism is closely related to the improvement of vascular calcification (VC) in chronic kidney disease (CKD). Globular adiponectin (gAd) has been reported to be involved in the development of VC in CKD, but the detailed regulatory role remains unclear. The present study is aimed to investigate the biological function and the underlying regulation mechanism of gAd in the process of VC during CKD. Vascular smooth muscle cells (VSMCs) calcification was determined by Alizarin Red S staining. Protein signaling related with VC was tested by western blotting. The expression and intracellular localization of runt-related transcription factor 2 (Runx2) was detected by immunofluorescence and uraemic rat with VC was established by a two-step nephrectomy. Combined with the results of Alizarin Red S staining, we discovered that β-glycerophosphate (β-Gp)-induced the osteoblastic differentiation of VSMCs was significantly reversed by gAd treatment. Along with the VSMCs calcification and the increase of Runx2 in β-Gp-exposed VSMCs, the activities of protein kinase B (AKT) and Wnt/β-catenin pathway were enhanced, but that were counteracted by the exposure of gAd in rat and human VSMCs. After administration with agonists of the Wnt (SKL2001) and AKT (SC79), there appeared more osteoblastic differentiation and higher expression of Runx2 in gAd-treated VSMCs, but showing lower impact in the presence of SC79 than that in the presence of SKL2001. In the in vivo experiments, intravenous injection of gAd also significantly inhibited VC and Runx2 level in uraemic rat in a dose-dependent manner, possibly through regulating Wnt/β-catenin pathway. This study demonstrates that gAd ameliorates osteoblastic differentiation of VSMCs possibly by blocking PI3K/AKT and Wnt/β-catenin signaling transduction. The findings provide an important foundation for gAd in treating VC in kidney diseases.

Emerging role of air pollution in chronic kidney disease - Yue Chen; Fan Cao; Jian-Ping Xiao; Xin-Yu Fang; Xue-Rong Wang; Li-Hong Ding; De-Guang Wang; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

The rescue and selection of thermally stable type O vaccine candidate strains of foot-and-mouth disease virus - Ya Gao; Pinghua Li; Xueqing Ma; Xingwen Bai; Pu Sun; Ping Du; Hong Yuan; Yimei Cao; Kun Li; Yuanfang Fu; Jing Zhang; Huifang Bao; et al. (Archives of Virology, 2021)

Increasing Temperature Alters the Effects of Extracellular Copper on Thalassiosira Pseudonana Physiology and Transcription - Xinjie Wang; Wang Cao; Hong Du; Wenhua Liu; Ping Li (Journal of Marine Science and Engineering, 2021)
Copper (Cu) is essential for many physiological processes in phytoplankton, including electron-transfer reactions and high-affinity Fe transport systems. However, at high concentrations, Cu can have a toxic effect on phytoplankton. Phytoplankton’s tolerance to certain toxicants in marine ecosystems cannot always be solely attributed to the presence of compounds, as various environmental factors including temperature can also indirectly influence their effects on organisms. In this study, we investigated the effects of different Cu concentrations (0, 19.6, 160, 800, and 8000 nM) on the growth and physiological changes in the centric diatom Thalassiosira pseudonana (CCMP 1335) when simultaneously applied with temperature cultivation of 20 °C and 25 °C. At low (0 nM) and high (8000 nM) Cu concentrations, the growth rate of T. pseudonana was inhibited, though an increase in temperature lessened this inhibition. There were no significant changes in the POC:PON ratio during all of the treatments. However, increasing the temperature significantly decreased the POC: POP, PON: POP and BSi: POP ratios of T. pseudonana. The intracellular Cu content of T. pseudonana varied from 0.13 to 13.28 fg cell−1 in response to increases in ambient Cu concentrations. Lastly, an increase in the Cu concentration decreased the transcriptional expression of CTR (copper transporter), 3Hfcp (photosynthetic protein), and Sit1 (silica shell formation) encoding genes. In conclusion, our results indicated that T. pseudonana can adapt to physiological processes and molecular mechanisms in response to varying Cu concentrations and ambient temperatures.

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Detecting freeze–thaw damage degradation of sandstone with initial damage using NMR technology - Taoying Liu; Chaoyang Zhang; Jiangteng Li; Keping Zhou; Cao Ping (Bulletin of Engineering Geology and the Environment, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Exposed to Mercury-Induced Oxidative Stress, Changes of Intestinal Microflora, and Association between them in Mice - Yulan Zhao; Changming Zhou; Xiaoquan Guo; Guoliang Hu; Guyue Li; Yu Zhuang; Huabin Cao; Lin Li; Chonghong Xing; Caiying Zhang; Fan Yang; Ping Liu (Biological Trace Element Research, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Sediment Characteristics, Sources, and Transport Patterns in Kompong Som Bay, Cambodia: Indications from Grain Size and Heavy Minerals - Jinqing Liu; Xiaoying Chen; Ping Yin; Ke Cao; Fei Gao; Yuanku Meng; Jiandong Qiu; Meina Li (Journal of Ocean University of China, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Exploring the hydrologic response to the urban building coverage ratio by model simulation - Runxiang Cao; Fawen Li; Ping Feng (Theoretical and Applied Climatology, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Alternative complement pathway is activated in the brains of scrapie-infected rodents - Cao Chen; Yan Lv; Chao Hu; Xiao-Feng Xu; Ren-Qing Zhang; Kang Xiao; Yue Ma; Li-Ping Gao; Jian-Le Li; Qiang Shi; Jing Wang; Qi Shi; et al. (Medical Microbiology and Immunology, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Nitrate removal from groundwater using negatively charged nanofiltration membrane - Lianpei Zou; Sitong Zhang; Jianyong Liu; Yi Cao; Guangren Qian; Yu-You Li; Zhi Ping Xu (Environmental Science and Pollution Research, 2019)

An experimental study on the corrosion characteristics of the karst tunnel engineering area in Southwest China - Fugang Wang; Yanjie Zhao; Chuang Li; Cangsong Li; Tianshan Lan; Shifei Ping; Yuqing Cao (Bulletin of Engineering Geology and the Environment, 2019)

Combined expression and prognostic significance of PPFIA1 and ALG3 in head and neck squamous cell carcinoma - Hong Zhou; Ting Cao; Wen Ping Li; Gang Wu (Molecular Biology Reports, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Joint inversion method for interval quality factor based on amplitude and phase information - Dan-Ping Cao; Yue Li; Wen-Guo Sun; Kai Liang (Applied Geophysics, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Correction to: Molecular characterization of a novel citrivirus from citrus using next‑generation sequencing - Mengji Cao; Ping Li; Song Zhang; Fangyun Yang; Yan Zhou; Xuefeng Wang; Ruhui Li; Zhongan Li (Archives of Virology, 2018)

Molecular characterization of a novel citrivirus from citrus using next-generation sequencing - Mengji Cao; Ping Li; Song Zhang; Fangyun Yang; Yan Zhou; Xuefeng Wang; Ruhui Li; Zhongan Li (Archives of Virology, 2018)

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Effects of Rhizoma Alismatis extract on biochemical indices and adipose gene expression in oleic acid-induced hepatocyte injury in Jian carp (Cyprinus carpio var. Jian) - Jinliang Du; Rui Jia; Li-ping Cao; Weidong Ding; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2018)

Wideband dipole logging based on segment linear frequency modulation excitation - Xue-Shen Cao; Hao Chen; Ping Li; Hong-Bin He; Yin-Qiu Zhou; Xiu-Ming Wang (Applied Geophysics, 2018)

Molecular characterization of a novel luteovirus infecting apple by next-generation sequencing - Pan Shen; Xin Tian; Song Zhang; Fang Ren; Ping Li; Yun-qi Yu; Ruhui Li; Changyong Zhou; Mengji Cao (Archives of Virology, 2018)

Experimental and numerical investigation on the effect of moisture on coal permeability - Yuan Zhao; Shugang Cao; Yong Li; Hongyun Yang; Ping Guo; Guojun Liu; Ruikai Pan (Natural Hazards, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Effect of Temperature–Water Coupled Actions on Joint Morphology - Jing-shuo Liu; Ping Cao; Jie Liu; Jin-xing Fan; Guo-guo Ning; Fu-liang Li (Geotechnical and Geological Engineering, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Fluid inclusions and C-H-O-S isotope systematics of early Permian porphyry Mo mineralization of the West Junggar region, NW China: the Suyunhe example - Chong Cao; Ping Shen; Changhao Li; Guoping Zheng (International Geology Review, 2017)

Carboniferous porphyry Cu (-Au) mineralization of the West Junggar region, NW China: the Shiwu example - ChangHao Li; Ping Shen; HongDi Pan; Wei Huang; Chong Cao (International Geology Review, 2017)

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Genetic diagnosis of a Chinese multiple endocrine neoplasia type 2A family through whole genome sequencing - Zhen-Fang Du; Peng-Fei Li; Jian-Qiang Zhao; Zhi-Lie Cao; Feng Li; Ju-Ming Ma; Xiao-Ping Qi (Journal of Biosciences, 2017)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

The Brain NO Levels and NOS Activities Ascended in the Early and Middle Stages and Descended in the Terminal Stage in Scrapie-Infected Animal Models - Li-Na Chen; Jing Sun; Xiao-Dong Yang; Kang Xiao; Yan Lv; Bao-Yun Zhang; Wei Zhou; Cao Chen; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2017)

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells - Xiaojie Cao; Lili Zhang; Chunhai Chen; Qingsong Wang; Lu Guo; Qinlong Ma; Ping Deng; Gang Zhu; Binghu Li; Yan Pi; Chunyan Long; Lei Zhang; et al. (Cell and Tissue Research, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

Erratum to: Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Fine mapping and candidate gene analysis of qHD5, a novel major QTL with pleiotropism for yield-related traits in rice (Oryza sativa L.) - Bin Sun; Xiao-Deng Zhan; Ze-Chuan Lin; Wei-Xun Wu; Ping Yu; Ying-Xin Zhang; Lian-Ping Sun; Li-Yong Cao; Shi-Hua Cheng (Theoretical and Applied Genetics, 2017)

Remote sensing Penman–Monteith model to estimate catchment evapotranspiration considering the vegetation diversity - Fawen Li; Runxiang Cao; Yong Zhao; Dongjing Mu; Changfeng Fu; Feng Ping (Theoretical and Applied Climatology, 2017)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

Tight regulation of the interaction between Brassica napus and Sclerotinia sclerotiorum at the microRNA level - Jia-Yi Cao; You-Ping Xu; Li Zhao; Shuang-Sheng Li; Xin-Zhong Cai (Plant Molecular Biology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The Levels of Tau Isoforms Containing Exon-2 and Exon-10 Segments Increased in the Cerebrospinal Fluids of the Patients with Sporadic Creutzfeldt-Jakob Disease - Cao Chen; Wei Zhou; Yan Lv; Qi Shi; Jing Wang; Kang Xiao; Li-Na Chen; Bao-Yun Zhang; Xiao-Ping Dong (Molecular Neurobiology, 2016)

A New Methodology for Open Pit Slope Design in Karst-Prone Ground Conditions Based on Integrated Stochastic-Limit Equilibrium Analysis - Ke Zhang; Ping Cao; Guowei Ma; Wenchen Fan; Jingjing Meng; Kaihui Li (Rock Mechanics and Rock Engineering, 2016)

Stability Analysis of Rock Slope Controlled by Major Geological Discontinuities Based on the Extended Kinematical Element Method - Ke Zhang; Ping Cao; Guowei Ma; Feng Ren; Kaihui Li (Rock Mechanics and Rock Engineering, 2016)

Cholangiocarcinoma-derived exosomes inhibit the antitumor activity of cytokine-induced killer cells by down-regulating the secretion of tumor necrosis factor-α and perforin - Jiong-huang Chen; Jian-yang Xiang; Guo-ping Ding; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

High expression of growth factor receptor-bound protein 14 predicts poor prognosis for colorectal cancer patients - Ping Yang; Jianchang Wei; Wanglin Li; Feng He; Shanqi Zeng; Tong Zhang; Zheng Sun; Jie Cao (Biotechnology Letters, 2016)

Increasing the immune activity of exosomes: the effect of miRNA-depleted exosome proteins on activating dendritic cell/cytokine-induced killer cells against pancreatic cancer - Ri-sheng Que; Cheng Lin; Guo-ping Ding; Zheng-rong Wu; Li-ping Cao (Journal of Zhejiang University-SCIENCE B, 2016)

Fatal pneumonia cases caused by human adenovirus 55 in immunocompetent adults - Shu-Yan Zhang; Yan-Ping Luo; Dou-Dou Huang; Hang Fan; Qing-Bin Lu; Ying Wo; Gang Chen; Xiao-Ai Zhang; Yan Li; Yi-Gang Tong; Wu-Chun Cao; Wei Liu (Infectious Diseases, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

Remarkable Activation of the Complement System and Aberrant Neuronal Localization of the Membrane Attack Complex in the Brain Tissues of Scrapie-Infected Rodents - Yan Lv; Cao Chen; Bao-Yun Zhang; Kang Xiao; Jing Wang; Li-Na Chen; Jing Sun; Chen Gao; Qi Shi; Xiao-Ping Dong (Molecular Neurobiology, 2015)

A Study on Isotropic Rock Breaking with TBM Cutters Under Different Confining Stresses - Jie Liu; Ping Cao; Kaihui Li (Geotechnical and Geological Engineering, 2015)

Bioaccumulation and Elimination of the Herbicide Clomazone in the Earthworms Eisenia fetida - Jia Cao; Ping Li; Qing X. Li; Pengfei Zheng; Xiaoping Diao (Bulletin of Environmental Contamination and Toxicology, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Scrapie Infection in Experimental Rodents and SMB-S15 Cells Decreased the Brain Endogenous Levels and Activities of Sirt1 - Jing Wang; Jin Zhang; Qi Shi; Bao-Yun Zhang; Cao Chen; Li-Na Chen; Jing Sun; Hui Wang; Kang Xiao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2015)

Modeling the Progressive Failure of Jointed Rock Slope Using Fracture Mechanics and the Strength Reduction Method - Ke Zhang; Ping Cao; Jingjing Meng; Kaihui Li; Wenchen Fan (Rock Mechanics and Rock Engineering, 2015)

Erythropoietin (EPO) Protects Against High Glucose-Induced Apoptosis in Retinal Ganglional Cells - Yunxiao Wang; Hui Zhang; Yanping Liu; Ping Li; Zhihong Cao; Yu Cao (Cell Biochemistry and Biophysics, 2015)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Impacts of polar vortex, NPO, and SST configurations on unusually cool summers in Northeast China. Part I: Analysis and diagnosis - Yi Lian; Baizhu Shen; Shangfeng Li; Bin Zhao; Zongting Gao; Gang Liu; Ping Liu; Ling Cao (Advances in Atmospheric Sciences, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Comparative analysis of essential oil components of Evodia rutaecarpa (Juss.) Benth. var. officinalis (Dode) Huang and Evodia rutaecarpa (Juss.) Benth. - Guang-Xian Cai; Dan Huang; Shun-Xiang Li; Fei Xu; Lu Wang; Yan-Hui Lu; Liang Cao; Bao-Yang Wei; Ya Li; Ping Cai (Natural Product Research, 2012)

Association of the microRNA-499 variants with susceptibility to hepatocellular carcinoma in a Chinese population - Yu Xiang; Song Fan; Ju Cao; Shifeng Huang; Li-ping Zhang (Molecular Biology Reports, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuanqin Xu; Peiying Li; Ping Li; Lejun Liu; Chengxiao Cao; Xiuli Feng (Marine Georesources & Geotechnology, 2012)

The different expression of immune-related cytokine genes in response to velogenic and lentogenic Newcastle disease viruses infection in chicken peripheral blood - Wen-Quan Liu; Ming-Xing Tian; Yuan-Ping Wang; Yang Zhao; Nian-Li Zou; Fang-Fang Zhao; San-Jie Cao; Xin-Tian Wen; Ping Liu; Yong Huang (Molecular Biology Reports, 2012)

Saline conducted electric coagulation (SCEC): original experience in experimental hepatectomy - Guo-ping Ding; Li-ping Cao; Da-ren Liu; Ri-sheng Que (Journal of Zhejiang University-SCIENCE B, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Rapid determination of melamine in milk using water-soluble CdTe quantum dots as fluorescence probes - Minwei Zhang†; Hong Ping†; Xianyi Cao; Hongkun Li; Fengrui Guan; Chunyan Sun; Jingbo Liu (Food Additives & Contaminants: Part A, 2011)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuan-Qin Xu; Pei-Ying Li; Ping Li; Le-Jun Liu; Cheng-Xiao Cao; Xiu-Li Feng (Marine Georesources & Geotechnology, 2011)

Transumbilical single-port laparoscopic cholecystectomy using traditional laparoscopic instruments: a report of thirty-six cases - Li-ping Cao; Ri-sheng Que; Fan Zhou; Guo-ping Ding; De-xi Jing (Journal of Zhejiang University-SCIENCE B, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Proteomics analysis of plasma membrane from liver sinusoidal endothelial cells after partial hepatectomy by an improved two-dimensional electrophoresis - Xuanwen Li; Li Xiong; Chunliang Xie; Jia Cao; Huobao Deng; Yong Lin; Rui Cao; Jianglin Li; Ping Chen; Songping Liang (Molecular and Cellular Biochemistry, 2010)

Genetic analysis revealed LX4 genotype strains of avian infectious bronchitis virus became predominant in recent years in Sichuan area, China - Nian-Li Zou; Fang-Fang Zhao; Yuan-Ping Wang; Ping Liu; San-Jie Cao; Xin-Tian Wen; Yong Huang (Virus Genes, 2010)

Incidence and risk of significantly raised blood pressure in cancer patients treated with bevacizumab: an updated meta-analysis - Mao Mao An; Zui Zou; Hui Shen; Ping Liu; Meng Li Chen; Yong Bing Cao; Yuan Ying Jiang (European Journal of Clinical Pharmacology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Molecular analysis of grass carp (Ctenopharyngodon idella) by SRAP and SCAR molecular markers - Wei-dong Ding; Zhe-ming Cao; Li-ping Cao (Aquaculture International, 2010)

RNA interference effectively degrades mRNA and inhibits protein expression of GBV-C E2 gene in Huh7 cells - Ming-Mei Cao; Gang Li; Hao Ren; Wei Pan; Ping Zhao; Zhong-Tian Qi (Virus Genes, 2009)

Selection of housekeeping genes for gene expression studies on the development of fruit bearing shoots in Chinese jujube (Ziziphus jujube Mill.) - Hai-feng Sun; Yu-ping Meng; Gui-mei Cui; Qiu-fen Cao; Jie Li; Ai-hua Liang (Molecular Biology Reports, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

No spatial memory deficit exists in Kunming mice that recently recovered from motor defects following 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Jian-Bo Ni; Chun-Yan Cao; Jie-Ping Zhang; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2009)

Physiological Stress of High NH 4 + Concentration in Water Column on the Submersed Macrophyte Vallisneria Natans L. - Te Cao; Ping Xie; Zhongqiang Li; Leyi Ni; Meng Zhang; Jun Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Nitrogen losses from integrated rice–duck and rice–fish ecosystems in southern China - Li Cheng-fang; Cao Cou-gui; Wang Jin-ping; Zhan Ming; Yuan Wei-ling; Shahrear Ahmad (Plant and Soil, 2008)

Synthesis of lactosylated piperazinyl porphyrins and their hepatocyte-selective targeting - He-Ping Li; Zhong Cao; Hua-Wu Xiao (Medicinal Chemistry Research, 2008)

Effect of lead on ERK activity and the protective function of bFGF in rat primary culture astroglia - Ying Zhang; Li-ping Ye; Biao Wang; Shi-cheng Cao; Li-guang Sun (Journal of Zhejiang University-SCIENCE B, 2007)

Economic approach for control agricultural nonpoint source pollution in China - Xiao-yan Wang; Li-ping Cao (Chinese Geographical Science, 2005)

Evolution and development of Guangzhou-Hong Kong corridor - Ping Li; Xiao-shu Cao (Chinese Geographical Science, 2005)

Reduction of nitrobenzene with H2 using a microbial consortium - Hong-Bin Cao; Yu-Ping Li; Gui-Feng Zhang; Yi Zhang (Biotechnology Letters, 2004)

Expression Profile of the Channel Catfish Spleen: Analysis of Genes Involved in Immune Functions - Arif M. Kocabas; Ping Li; Dongfeng Cao; Attila Karsi; Chongbo He; Andrea Patterson; Zhenlin Ju; Rex A. Dunham; Zhanjiang Liu (Marine Biotechnology, 2002)